Diseño de una central generadora eólica para un sistema de bombeo hídrico en la comunidad de maca atápulo parroquia poaló cantón Latacunga provincia de Cotopaxi. - Paredes Mejía, Andrés Eduardo (2019)
The Ecuadorian energy system is based on electrical generators which the primary energy sources consist of fossil origin and renewable energies, the latter being the most weight in the total production of electric power available within Ecuador. In the figures of Ecuadorian electricity generation, we have a small proportion in the exploitation of wind energy, being used in our country in San Cristóbal Island with 2.4 MW of capacity and in the province of Loja on Cerro Villonaco with 16.5 MW. The research that is presented, is directed to the study of the potential of the wind energy for generation of electric energy in the zone known as Hills of Milin, high zone of the Andean Mountain range, located in the limits of the municipalities of Pujilí Canton and the Saquisili Canton. Where it is determined by bibliographic research and a field study with the application of a meteorological station, the different components and parameters that affect the wind generation systems as observed in these surfaces and that can be affected by the air flows varying the pressure fields, all this determining the existence of persistent local winds in seasonal cycles, thus obtaining the existence of the wind resource for the application and design of an optimal power plant, capable of satisfying the power demand of a water pumping system benefiting approximately 700 inhabitants in the community of "Maca Atápulo" located in the Poaló parish, Latacunga canton, Cotopaxi province. For this, it is necessary to analyze the wind potential of the Milin hills, establishing aerodynamic conditions that provide the highest performance when converting the available kinetic energy into the air current, into electrical energy obtaining the greatest potential in our work area.